Tragedi di Pulau ‘Seribu Mesjid’: Konflik Agama atau Perlawanan Budaya? - Mahsun Mahsun (Antropologi Indonesia, 2000)
There are a set of questions that needs to be answered in relation to the Mataram tragedy which has been known as the 'Tragedy One Seven One' (Tragedy Satu Tujuh Satu). One of the question is: if the tragedy has the basis of religious conflict, why did the conflict occur only between the Moslems and the Christians, and not between the Moslems and the Hindus which has a greater number of followers than the Christians? By looking at the main target of the tragedy, the churches, not the individuals, as well as its short duration, a cultural analysis is the most probable way to find relevant answers. The author argues that the Mataram tragedy was not staying apart from the development of an increasing number of churches. The building of Christian churches, their quantity, quality, and geographical distribution was seen as the emergence of the new opposed culture. The latter was perceived as threatening the culture of 'Thousand Mosques', the native ethnic identity, and the majority of the people of Pulau Lombok. In this article, the author examines the culture of 'Thousand Mosques', its relation to the Mataram tragedy.